A progressive collapse modelling strategy coupling the yield design theory with non-linear analysis. (15th August 2021) - El Hajj Diab, Mohammad; Orcesi, André; Desprez, Cédric; Bleyer, Jérémy
Highlights: A progressive collapse modelling approach is proposed. A coupling between yield design and non-linear analyses is introduced. One investigates the ability of the structure to develop an alternative equilibrium. The numerical modelling of the proposed approach is detailed. A steel framed case study is considered for illustration of the proposed concepts. Abstract: Several examples of structures have been severely damaged, or even reached the total collapse, after the propagation of some local failure, resulting from an accidental or exceptional event. These catastrophic events highlight the importance of not limiting safety assessment in structural design under identified conditions, but also to investigate how much the structural integrity can be preserved so that progressive collapse is avoided under an exceptional event unidentified at the design stage. The main objective of this work is to propose a progressive collapse modelling approach in order to characterize structural robustness. Considering the occurrence of some exceptional event, the yield design theory is used to identify the part of the structure concerned by a failure mechanism. As the yield design theory is based on the infinitesimal strain assumption, an iterative coupling between the yield design approach and a non-linear analysis of the directly affected part is proposed to (i) better analyze the structural response of the part concerned by the failure mechanism, (ii) consider the development of materials and geometrical non-linearities, and (iii) model progressive collapse within the structure. The successive iterations of the yield design approach including the deformed geometrical configuration allow to check the potential ability of the structure to develop a second line of defence. This coupling strategy is applied to a steel framed structure for illustration of the proposed concepts.